Vnitropodniková komunikace ve vybrané společnosti - Rampulová, Kateřina (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Diplomová práce se zabývá problematikou interní komunikace ve vybrané společnosti. Teoretická východiska práce odhalují poznatky o komunikaci jako takové a o komunikaci uvnitř firmy. Praktická část analyzuje aktuální stav vnitropodnikové komunikace v daném podniku prostřednictvím dotazníkového šetření. Na základě výsledků tohoto šetření jsou pro firmu navrhnuta doporučení vedoucí k zefektivnění vnitropodnikové komunikace.

The diploma thesis concerns the internal communication in the company which I have selected. The theoretical part of the thesis describes generally the findings about communication and internal communication. The body focuses on an analysis of the internal communication within the selected company, using the questionnaire. The analysis includes recommendations based on the results of the survey, which could enhance the effectiveness of internal communication within the company structure.
Internal Communication in Selected Company.
Keywords: Interní komunikace; přenos informací; komunikační dovednosti; motivace.; Internal communication; information flow; communication skills; motivation.